Notes on the genus Microtachycines Gorochov, 1992 and establishment of a new genus from China (Rhaphidophoridae: Aemodogryllinae) - Zhu, Qi-Di; Shi, Fu-Ming; Zhou, Zhi-Jun (European Journal of Taxonomy, 2022)
This paper reviews the genus Microtachycines and establishes a new genus, Megatachycines gen. nov. One new species and two new combinations of the genus Megatachycines are recorded, i.e., Megatachycines pentus gen. et sp. nov., Megatachycines elongatus (Qin, Liu & Li, 2017) comb. nov., and Megatachycines trispinosus (Qin & Li, 2020) comb. nov. Images illustrating the morphology of all species of the genera Microtachycines and Megatachycines are provided.